A Malaysian perspective on Lithium-ion Batteries recycling - Bahrudin, Fadzli Irwan; Daud, Nuraini; Harun, Irina; Aizamddin, Muhamad Faiz; Shafee, Siti Nur Amira; Mahat, Mohd Muzamir (Springer Nature, 2024)
Lithium-ion batteries (LIBs) have been widely used in various applications including portable devices, electric vehicles, and large-scale energy storage systems. Compared to other battery types, LIBs have a high power density, relatively higher cycle life, long run time, good discharge or charge cycles, and low cost. The use of LIBs aligns with a global-wide strategy in pursuing sustainable development and a circular economy as it helps decarbonize the transportation and power sectors. As such, Li supply has a heavy burden, and the demand will consistently hike soon. Therefore, re-circulating spent LIBs from industries or consumers’ waste is a promising strategy. To secure a closed loop of Li, consumers need to embrace positive environmental stewardship by returning used e-waste to the recycling entry points. Then, the non-renewable resources would be passed over to a number of stakeholders and go through a sequence of recycling processes before re-entering the usage loop. In pursuit of tracking the lifecycle of spent Lithium-ion Batteries (LiBs), this article undertakes an initial examination of electronic waste (e-waste) resource dynamics within the context of Malaysia. Through document analysis of data from sixty-three e-waste recycling stakeholders’ websites, the study has categorized the phases of e-waste flows, based on the recycling processes. According to the data, a noteworthy proportion of recycling stakeholders are involved in the preliminary phase of the ‘resource entry point’, whereas a comparatively small fraction of them engages in the subsequent phase of ‘resource segregation’. Conversely, a meager number of recyclers are involved in ‘resource extraction’, particularly concerning the ‘retrieve’ activities. Notably, data on detailed activities within each phase is fragmented and there is currently no evidence found on active LiBs recycling activities in Malaysia. With strategic effort, there are achievable potentials for efficient e-waste circular flows in Malaysia, where valuable resources like Li can be extracted. Recycling interventions, infrastructure, and legislation are among the integral aspects to be researched and designed, to optimize e-waste circularity in Malaysia.